Does endoscopy of difficult to catheterize channels spare some patients from formal open revision?. Issue 4 (August 2016) - Casey, Jessica T.; Zhang, Mimi; Chan, Katherine H.; Szymanski, Konrad M.; Judge, Benjamin; Whittam, Benjamin; Kaefer, Martin; Misseri, Rosalia; Rink, Richard C.; Cain, Mark P.
Summary: Introduction: Patients with continent catheterizable channels (CCC) may develop difficulty catheterizing postoperatively. In complex cases, endoscopic evaluation with indwelling catheter placement may be indicated, but the risk factors for subsequent formal channel revision are not well defined. The purpose of this study was to determine the risk factors for formal channel revision after attempted endoscopic management of difficulty catheterizing. Materials and methods: We performed an IRB-approved retrospective review of pediatric (<21 years old) patients undergoing CCC construction at our institution from 1999 to 2014 to identify patients who underwent endoscopy for difficulty catheterizing. Fisher's Exact test was used for categorical data and Mann–Whitney U test for continuous variables to examine the association between endoscopic intervention and subsequent formal revision. Results: Sixty-three of 434 patients (14.5%) underwent at least one endoscopy for reported difficulty catheterizing their CCC, with 77.8% of these requiring additional intervention during endoscopy (catheter placement, dilation, etc.). Of these, almost half with functioning channels (43.5%, 27/62) were managed successfully with endoscopy without formal revision; six (22.2%) of whom underwent more than one endoscopy. These 27 patients continued to catheterize well at a median follow-up of 3.2 years (interquartile range 2.0–6.0). Patients requiring revision had a median of 1.7 years between CCC creation and first endoscopy, versus 1.6 years in those who were not revised ( p = 0.60). There was no statistically significant difference between revised and non-revised channels in terms of patient age at CCC creation, underlying patient diagnosis, status of bladder neck, stomal location, or channel type ( p ≥ 0.05) (seeTable ). Conclusion: Approximately half of our patients did not require a formal channel revision after endoscopic management. We did not identify any specific risk factors for subsequent formal revision of a CCC. We recommend performing at least one endoscopic evaluation for those with difficulty catheterizing prior to proceeding with formal open revision. Table Patient demographics. Revised ( n = 35) Not revised ( n = 27) Patient age (years) at CCC creation, median (IQR) 7.3 (5.4–9.8) 7.2 (5.8–10.4) p = 0.93 Gender p = 0.62 Female, n (%) 16 (45.7) 14 (51.9) Male, n (%) 19 (54.2) 13 (48.1) Diagnosis p = 0.36 Spina bifida, n (%) 29 (82.8) 19 (70.4) Other, n (%) 6 (17.1) 8 (29.6) Bladder neck p = 0.86 Closure, n (%) 3 (8.6) 2 (7.4) Sling or reconstruction, n (%) 16 (45.7) 10 (37.0) Native, n (%) 16 (45.7) 15 (55.6) Stomal location p = 0.10 Umbilical, n (%) 14 (40.0) 5 (18.5) Non-umbilical, n (%) 21 (60.0) 22 (81.5) Channel type p = 0.11 Appendicovesicostomy, n (%) 4 (11.4) 8 (29.6) Monti ileovesicostomy, n (%) 31 (88.6) 19 (70.4)